Comparison of economic load dispatch problem by using Particle Swarm Optimization (PSO) and Evolutionary Programming (EP) / Ku Azila Ku Teh - Ku Teh, Ku Azila (2013)
Economic Load Dispatch (ELD) is a problem in power system that arise in scheduling the generation unit in order to minimizing the cost and at the same time satisfying the constraints. Most of generating units nowadays use fossil fuel as energy source. However, fossil fuels are depleting from day to day and the demand for electricity is increasing. This situation causes the price of fossil fuel is also increasing. Due to the importance of Economic Load Dispatch (ELD) in power system, many techniques have been introduced to solve ELD problem.